A review of backtesting for value at risk. Issue 15 (3rd August 2018) - Zhang, Y.; Nadarajah, S.
ABSTRACT: There have been many backtesting methods proposed for value at risk. Yet they have rarely been applied in practice. Here, we provide a comprehensive review of all of the recent backtesting methods for VaR. This review could encourage applications and also the development of further backtesting methods.